Innovative moments in low-intensity, telephone-based cognitive-behavioral therapy for depression - Drüge, Marie; Staeck, Robert; Haller, Elisa; Seiler, Cara; Rohner, Valentin; Watzke, Birgit (Frontiers in Psychology, 2023)
Background: Innovative moments (IMs) as moments in psychotherapy in which the patients’ problematic patterns change towards more elaborated and adaptive patterns, have been shown to be associated with clinical change in patients with depression. Thus far IMs have only been studied in face-to-face settings, but not in telephone-based Cognitive-Behavioral Therapy (t-CBT). This study investigates whether IMs occur in t-CBT and examines the association between IMs and symptom improvement, and Reconceptualization and symptom improvement. Methods: The therapy transcripts of n = 10 patients with mild to moderate depression (range: 7-11 sessions, in total 94 sessions) undergoing t-CBT were qualitatively and quantitatively analyzed. Symptom severity (Patient Health Questionnaire-9) and IMs (levels and proportions) were assessed for each therapy session. Hierarchical linear models were used to test the prediction models. Results: The rating of IMs was shown to be feasible and reliable using Innovative Moments Coding System (IMCS) (84.04% agreement in words coded), which is indicative of the applicability of the of the concept of IM in t-CBT. Only Reconceptualization IMs were shown to have a predictive value for treatment success (R²= 0.05, p = .01). Discussion: The results should be interpreted with caution due to the exploratory nature of this study. Due to the telephone setting, it was necessary to adapt the IMCS. Nonetheless, the extent of IMs identified in the low-threshold t-CBT investigated, was comparable to IMs in face-to-face-therapy. Further studies are needed to clarify the association between IMs and treatment success as a change process, especially for low intensity treatments.